Potensi Probioitik Sebagai Terapi Akne Vulgaris - Meyliana Suwanda; Putri Ulayya Anjaya (Yayasan Pendidikan Medika Indonesia, 2021)
Safe and effective therapeutic options for acne vulgaris are needed to overcome the side effects and increasing resistance to current antibiotic therapy. Probiotics are microorganisms which when consumed in adequate amounts can have a healthful effect on the host which have the potential to be an alternative to new therapeutic options. To find out more about the use of probiotics as a therapy for acne vulgaris, using the method, namely the study of literature from both national and international journals by summarizing the topic of discussion and comparing the results presented in the article. Several in-vitro and in-vivo studies have shown that probiotics topical or oral as an adjunctive therapy have an effective potential in the management of acne vulgaris therapy either directly by preventing the growth of opportunistic bacteria or as anti-inflammatory both topically and systemically. Indirectly, the role of probiotics can also change intestinal permeability so that it can reduce pathogenic bacteria that cause acne vulgaris and also its mechanism that can ferment glycerol which is effective for use in the management of acne vulgaris therapy.